PENINGKATAN HASIL BELAJAR PAI DENGAN METODE TEAM QIUZSISWA KELAS VI - Ernawati Ernawati (Universitas Tanjungpura, 2018)
The purpose of the research is to improve students achievement using Team Quiz method on the sixth grade of 07elementary school in East Pontianak, Pontianak City (Borneo). This research was Classroom Action Research, using John Elliotl model. The subjects were sixth grade students. The data were collected through achievement test, observation sheets, questionnaires, and documentation. The data were analyzed using descriptive quantitative and qualitative analysis.The results show that the implementation of Team Quiz method can improve the process and the results of religion studies on the sixth grade. The improvement of learning process shown by students that are more active and communicative. In addition, the results indicated by the percentage of completeness in pre-action amounted to 41,93%, 61,29% in the first cycle, and 90,32% in the second cycle.